Impact of healthcare-associated infections on in-hospital outcomes during the COVID-19 era: a multicenter comparative study of 20,942 isolated microorganisms from ICU patients - Khavandegar, Armin; Siami, Zeinab; Rasouli, Aziz; Nazemi, Pershang; Gull, Anoosha (Frontiers in Public Health, 2025)
BackgroundHealthcare-associate infection (HAI) has been one of the health care issues worldwide. During the COVID-19 pandemic, HAI prevention was considered a vital aspect of the clinical management of COVID-19. In the present study, we aimed to compare the frequency of HAIs in ICU-admitted cases within and before the COVID-19 era.MethodsThis multicenter retrospective study applied a descriptive-analytical approach to investigate the frequency of HAIs in the ICU departments of hospitals affiliated with Tehran University of Medical Sciences from 2017 to 2022.ResultsOverall, 14,268 cases with 20,942 isolated microorganisms were recruited for this study, with 8,289 (58.1%) of them being male and 5,975 (41.9%) being female. A total of 6,722 (47.1%) cases with 9,917 (47.4%) isolated microorganisms were documented in the pre-COVID-19 era, while 7,546 (52.9%) patients with 11,025 (52.64%) were reported in COVID-19 era. Of 14,268 patients admitted to the ICU during the study period, 9,197 (64.8%) were discharged and 5,071 died (35.5%), of which 1,970 (29.3%) occurred in pre-COVID and 4,752 (70.7%) in the COVID-19 era (p-value < 0.001). Klebsiella species, Acinetobacter species, Escherichia coli, Staphylococcus species, and Pseudomonas aeruginosa were the five most frequent isolated microorganisms, reported in 5,542 (26.50%), 4,171 (19.90%), 2,651 (12.70%), 2,537 (12.10%), and 1,851 (8.80%) cultures, respectively. VAEs were the most common infection types as reported in 3,562 (25%) patients. There was a statistically significant difference in UTI, PMEU, BSI, and others, with an increase in PMEUs (13.5% vs. 17.1%) and BSI (22.7% vs. 24.5%) and a decrease in UTIs (24.5% vs. 22.2%) and others (4.2% vs. 2.6%) in COVID-19 era compared to pre-COVID-19. The odds of in-hospital mortality in all six main infection categories have significantly increased in the COVID-19 era when compared to the pre-COVID-19 era. The odds of death were increased in the SSI group more than the rest (OR:2.65, CI 95%: 2.13–3.29).ConclusionCOVID-19 changed the pattern of HAIs and also increased their mortality. Overall, the findings of this study emphasize the importance of continuous monitoring and improvement of infection control measures in ICUs to reduce the incidence of HAIs and improve patient outcomes.